Retinal nerve fiber layer thickness in children: the Ural children eye study - Bikbov, Mukharram; Kazakbaeva, Gyulli M.; Panda-Jonas, Songhomitra; Iakupova, Ellina M.; Jonas, Jost B. (Investigative ophthalmology & visual science, 2025)
To assess the peripapillary retinal nerve fiber layer thickness (RNFLT) in school children in Russia. The population-based school children study (Ural Children Eye Study [UCES]), performed in Ufa, Bashkortostan, Russia, included 4933 children (mean age, 9.7 ± 2.6 years; range, 6.2-18.8 years). The children underwent a series of ophthalmological and systemic examinations. The dependence of the fundus image magnification on axial length was corrected by the Littmann-Bennet method. Of 4933 children primarily participating in the UCES, 3111 (63.1%) underwent optical coherence tomography-based RNFLT measurement. The mean uncorrected RNFLT was 103.5 ± 11.3 µm, and after correction for axial length-related fundus image magnification, it was 99.9 ± 10.6 µm. A thicker RNFLT was associated on multivariable analysis with a higher birth weight (beta, 0.10; B, 0.002; 95% confidence interval [CI], 0.001-0.003; P < 0.001), a lower prevalence of maternal smoking during pregnancy (beta, −0.07; B, −8.49; 95% CI, −14.6 to −2.41; P < 0.001), higher school marks in mathematics (beta, 0.08; P = 0.006), higher cognitive function score (beta, 0.06; P = 0.005), and longer axial length (beta, 0.14; P < 0.001). RNFLT was thickest (P < 0.001) in the parapapillary inferior region (124.8 ± 18.7 µm) and superior region (124.8 ± 18.7 µm), thinner (P < 0.001) in the temporal region (77.1 ± 15.8 µm), and thinnest (P < 0.001) nasally (73.7 ± 16.3 µm). The nasal RNFLT decreased (beta, −0.07; B, −1.09; 95% CI, −1.65 to −0.54; P < 0.001), and the temporal RNFLT increased (beta, 0.34; B, 5.17; 95% CI, 4.67-5.67; P < 0.001) with a longer axial length. With a mean intereye difference in the RNFLT of 3.3 ± 5.5 µm, right and left eyes did not differ (P = 0.61) in RNFLT. In this ethnically mixed school children population from Russia, maternal smoking during pregnancy and birth weight lower by 250g decreased RNFLT by 8.5 µm and 5.0 µm, respectively. A thinner RNFLT correlated with worse cognitive scores and school marks. After adjusting for axial length, RNFLT increased with longer axial length.
Veröffentlicht: 14. November 2025
Gesehen am 29.01.2026